The impact of higher standards in patent protection for pharmaceutical industries under the TRIPS Agreement: A comparative study of China and India - Xuan Li (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
A comparative study is undertaken that explores Chinese and Indian pharmaceutical industries under different patent regimes. It is found that relative to India, which had implemented process patent until 2005, China with a product patent regime since 1993 suffers from both lower drug accessibility and availability (the latter is a missing parameter in the literature). Also, China lags behind in both lower R&D investment and patents filed by Chinese nationals. Based on these findings and associated legal interpretation, we conclude that higher patent protection in China generates negative impacts on the pharmaceutical industries. Thus, governments should utilize TRIPS flexibilities and other regimes like price control to offset the anticompetitive effect in designing patent policies.
Keywords: O34; L65; F14; 330; product patent; process patent; TRIPS; pharmaceutical industries; China; India; TRIPS; Patentrecht; Wohlfahrtseffekt; Pharmazeutische Industrie; China; Indien